Conductive adhesive, cylindrical lithium ion secondary battery and preparation method thereof

By using conductive glue to connect the end surface of the positive and negative electrode group of the lithium-ion secondary battery with the current collecting disk or shell, the existing batteries have solved the problems of large internal resistance fluctuations and safety hazards under high magnification and large capacity requirements, and the battery power performance, heat dissipation performance and service life are improved.

CN111564634BActive Publication Date: 2025-04-29DALIAN ZHONGBI ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010512811.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-08
Publication Date
2025-04-29
Estimated Expiration
2040-06-08

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries have problems such as large internal resistance fluctuations, safety hazards, low grouping efficiency, short service life and high cost under high magnification and large capacity requirements.

Method used

A conductive glue composed of silicone rubber, polyvinylidene fluoride, inorganic conductive agent and initiator is used to connect the end surface of the positive and negative electrode group to the current collecting disk or shell through the conductive glue to form a polymer conductive network to improve the conductivity and bonding strength of the battery.

Benefits of technology

It significantly improves the power and heat dissipation performance of the battery, reduces the short-circuit rate of the battery assembly process, improves the reliability and consistency of the battery structure, increases the coating area of ​​the pole sheet, and thus improves the capacity and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111564634B_ABST
    Figure CN111564634B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of energy storage batteries, and specifically relates to a conductive glue, a cylindrical lithium-ion secondary battery and a preparation method thereof. The conductive glue is made of raw materials including silicone rubber, polyvinylidene fluoride, an inorganic conductive agent and an initiator, wherein the mass ratio of the silicone rubber, polyvinylidene fluoride, the inorganic conductive agent and the initiator is 20-40:20-40:25-50:0.01-1. The cylindrical lithium-ion secondary battery includes a shell with an upper opening, a pole group arranged in the shell, a cap sealed at the upper opening of the shell, a current collecting plate arranged between the positive terminal of the pole group and the cap, the negative terminal of the pole group is bonded to the lower end of the shell by the conductive glue, and the positive terminal of the pole group is bonded to the current collecting plate by the conductive glue. The battery provided by the present invention has excellent power performance and heat dissipation performance, and the battery structure is reliable and the short circuit rate is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy storage batteries, and specifically relates to a conductive adhesive, a cylindrical lithium ion secondary battery and a preparation method thereof. Background Art

[0002] In the 21st century, it has become a trend for electric vehicles to replace fuel vehicles, and lithium-ion secondary batteries are an important component of electric vehicles. Electric vehicles can be divided into pure electric vehicles, plug-in hybrid electric vehicles, 48V micro-hybrid electric vehicles, etc. Among them, plug-in hybrid electric vehicles, especially 48V micro-hybrid electric vehicles, have very high requirements for the pulse charge and discharge rate of the battery. The pulse charge rate is required to be 20-35C, the pulse discharge rate is required to be 30-50C, and the single battery capacity is required to be 8Ah-20Ah.

[0003] Lithium-ion secondary batteries can be divided into cylindrical batteries, square batteries and soft-pack batteries according to the packaging process.

[0004] So far, the laminated soft-pack battery with multi-electrode design can better meet the above requirements, but the production process of soft-pack batteries is complicated; during use, the aluminum-plastic film shell is prone to leakage, which poses a safety hazard. In addition, the consistency between soft-pack battery cells is poor, the grouping efficiency is low, the service life is short, and the cost remains high.

[0005] Square batteries also have the advantages and disadvantages of the above-mentioned soft-pack batteries, and another disadvantage of square batteries is that their heat dissipation performance is worse than that of soft-pack batteries.

[0006] Cylindrical batteries are developed from Panasonic's 18650 small batteries, that is, the outer diameter of the battery is 18mm and the height is 65mm. Ordinary small cylindrical batteries use gap coating when making positive and negative electrodes. The purpose is to weld the strip-shaped pole ears. Insulating tape is required. Generally, the positive and negative electrodes can lead out a maximum of 3-4 pole ears. It can meet the charging and discharging requirements at a certain rate, but it cannot meet the high-rate charging and discharging requirements of micro-hybrid electric vehicles, and the capacity cannot meet the requirements. Usually, the maximum capacity is only 2-2.5Ah. However, cylindrical batteries have the characteristics of high production efficiency, high battery consistency, high grouping efficiency, long life, and low cost.

[0007] If the process of small cylindrical batteries is introduced into large cylindrical batteries, in order to ensure the input of current, the number of pole ears will inevitably increase exponentially, and the difficulty of welding the pole ears together will increase, which will easily lead to problems of cold welding, resulting in large fluctuations in the internal resistance of the battery and easy failure of the battery after being grouped. For this reason, people have proposed a solution: shaping the end face of the battery pole group, that is, flattening the foil shape of the end face of the pole group by high-frequency oscillation, and then performing laser welding of the collector plate. This method has the following defects: First, a certain amount of metal dust is easily generated during the flattening process of the positive electrode collector aluminum foil and the negative electrode collector copper foil, which may cause the battery to short-circuit and self-discharge at the least, and the dust may puncture the diaphragm, short-circuit the positive and negative electrodes, and cause the battery to catch fire and explode; second, when the collector plate is welded to the end face of the electrode group, due to the characteristics of laser welding, the welding of the collector plate and the end face of the electrode group can only be local spot welding, resulting in uneven distribution of current on the collector plate, affecting the power performance and heat dissipation performance of the battery; third, because the empty foil area of ​​the end face collector is large, the coating area of ​​the active material is reduced, and the energy density of the battery is reduced; fourth, steel shell packaging is adopted, and the negative electrode collector plate is generally connected to the bottom of the steel shell through a spot welding process, and the contact resistance is large. For charging and discharging currents above 50A, a large amount of heat is generated instantly, and the local temperature is far higher than the battery safety temperature of 80°C. Side reactions such as decomposition of the battery negative electrode SEI film, decomposition of the electrolyte, and decomposition of the positive electrode active material will occur, and the battery temperature will further increase, which is easy to cause safety problems such as thermal runaway. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a conductive adhesive, a cylindrical lithium-ion secondary battery and a preparation method thereof.

[0009] Specifically, the present invention provides the following technical solutions:

[0010] A conductive adhesive is made of raw materials including silicone rubber, polyvinylidene fluoride, an inorganic conductive agent and an initiator, wherein the mass ratio of the silicone rubber, polyvinylidene fluoride, inorganic conductive agent and the initiator is 20-40:20-40:25-50:0.01-1. The silicone rubber matrix provides fluidity, so that the conductive adhesive can be evenly applied to both ends of the electrode group, and cross-linking after heating provides a certain bonding strength. The polyvinylidene fluoride particles are heated and melted to form a polymer conductive network together with the inorganic conductive agent, and the polyvinylidene fluoride can produce strong adhesion with copper foil, aluminum foil, current collector, etc. The initiator promotes the thermal polymerization of the silicone rubber.

[0011] Preferably, in the above conductive adhesive, the mass ratio of the silicone rubber, polyvinylidene fluoride, inorganic conductive agent and the initiator is 30-35:30-35:30-39:0.01-1.

[0012] Preferably, in the above conductive adhesive, the silicone rubber is methyl silicone rubber, methyl vinyl silicone rubber or methyl vinyl phenyl silicone rubber;

[0013] And / or, the inorganic conductive agent is nano carbon black particles, carbon nanotubes, carbon fibers, graphene or VGCF;

[0014] And / or, the initiator is di-tert-butyl cumene peroxide (BIPB), dicumyl peroxide (DCP), benzoyl peroxide (BP) or 2,4-dichlorobenzoyl peroxide (DCBP).

[0015] The present invention also provides a cylindrical lithium-ion secondary battery, comprising a shell with an opening at the upper end, a pole group arranged in the shell, a cap sealed at the opening at the upper end of the shell, and a current collecting plate arranged between the positive end of the pole group and the cap, the negative end of the pole group is bonded to the lower end of the shell by the above-mentioned conductive adhesive, and / or the positive end of the pole group is bonded to the current collecting plate by the above-mentioned conductive adhesive.

[0016] Preferably, in the above cylindrical lithium-ion secondary battery, the thickness of the conductive adhesive layer formed by any conductive adhesive is 0-1 mm, that is, the overlap width of the conductive adhesive and the blank area of ​​the positive and negative electrode foils is 0-1 mm, more preferably 0.1-0.5 mm.

[0017] Preferably, in the above cylindrical lithium-ion secondary battery, the electrode group includes a positive electrode sheet, a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet includes a positive electrode coating area coated with a positive electrode active material and a positive electrode blank area not coated with a positive electrode active material, and the negative electrode sheet includes a negative electrode coating area coated with a negative electrode active material and a negative electrode blank area not coated with a negative electrode active material;

[0018] Among them, the width of the negative electrode blank area is 2-4mm, the width of either end of the diaphragm exceeds the width of the negative electrode coating area by 1-2mm, the width of the positive electrode blank area is 3-5mm, and the width of either end of the negative electrode coating area exceeds the width of the positive electrode coating area by 0.5-1mm.

[0019] Preferably, in the above cylindrical lithium-ion secondary battery, the current collecting plate and the cap are connected through a pole ear, the current collecting plate and the pole ear are fixed by laser welding, the material of the current collector is aluminum alloy, the material of the pole ear is aluminum alloy, and the other end of the pole ear is connected to the cap by laser welding.

[0020] Preferably, in the above cylindrical lithium-ion secondary battery, the shell is a steel shell, and the inner and outer surfaces of the steel shell are electroplated with nickel.

[0021] Preferably, in the above cylindrical lithium-ion secondary battery, the battery housing is provided with a rolling groove located on the tab, and the rolling groove surrounds the cylinder.

[0022] The present invention also provides a method for preparing a cylindrical lithium-ion secondary battery, comprising the following steps:

[0023] (1) Winding a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet to form an electrode group, and coating the above-mentioned conductive glue on the negative end of the electrode group;

[0024] (2) placing the electrode group obtained in step (1) into a casing with an upper opening with the negative terminal facing downward, and subjecting the electrode group to high temperature treatment to solidify the conductive agent at the negative terminal;

[0025] (3) The conductive adhesive is coated on the positive terminal of the electrode group, and then a current collecting plate is bonded to the positive terminal, and the conductive agent of the positive terminal is cured by high temperature treatment.

[0026] Preferably, in the above preparation method, after step (3), the step of injecting an electrolyte and sealing is also included; more preferably, the electrolyte comprises a solvent, a soluble lithium salt and an additive, the solvent is ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate or ethyl acetate, the soluble lithium salt is lithium hexafluorophosphate, and the additive is propane sultone, vinylene carbonate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, methylene disulfonate, lithium difluorooxalatophosphate or fluorocarbonate.

[0027] Preferably, the above preparation method comprises the following steps:

[0028] Preparation of battery electrode group: positive electrode slurry → continuous coating of positive electrode sheet → rolling of positive electrode sheet → cutting of positive electrode sheet → positive electrode sheet; negative electrode slurry → continuous coating of negative electrode sheet → rolling of negative electrode sheet → cutting of negative electrode sheet → negative electrode sheet; winding of positive and negative electrode sheets and separator to obtain electrode group;

[0029] Battery equipment: Glue coating on negative end of electrode group → electrode group into steel shell → high temperature melting and solidification of negative electrode glue → glue coating on positive end of electrode group → bonding of positive electrode collector plate → high temperature melting and solidification of positive electrode glue → roller trough → vacuum drying → liquid injection → sealing → formation and capacity separation.

[0030] Preferably, in the above preparation method, the positive electrode sheet is composed of a positive electrode active material, a first conductive agent, a first binder and a first current collector; more preferably, the positive electrode active material is lithium iron phosphate, lithium manganese oxide, nickel cobalt manganese lithium or lithium cobalt oxide, the first conductive agent is nano carbon black particles, carbon nanotubes, carbon fiber, graphene or VGCF, the first binder is polyvinylidene fluoride, styrene butadiene rubber latex or polyolefin nitrile, and the first positive electrode current collector is aluminum foil or carbon-coated aluminum foil; further preferably, the surface density of the positive electrode active material is 100-300 mg / 10 cm 2 .

[0031] Preferably, in the above preparation method, the negative electrode sheet is composed of a negative electrode active material, a second conductive agent, a second binder and a second current collector; more preferably, the negative electrode active material is artificial graphite, natural graphite, mesophase carbon microspheres, silicon oxide, silicon carbide or lithium titanate, the second conductive agent is nano carbon black particles, carbon nanotubes, carbon fibers, graphene or VGCF, the second binder is sodium carboxymethyl cellulose, styrene-butadiene rubber latex, polyvinylidene fluoride or polyolefin nitrile, and the second current collector is copper foil; further preferably, the surface density of the negative electrode active material is controlled to be α*B*C / D, wherein α is the negative electrode excess coefficient, B is the surface density of the positive electrode active material, C is the gram capacity of the positive electrode active material, and D is the gram capacity of the negative electrode active material.

[0032] Preferably, in the above preparation method, the diaphragm is a polypropylene single-layer film, a polyethylene single-layer film or a polypropylene-polyethylene-polypropylene three-layer composite film, or a composite diaphragm composed of the above diaphragm and ceramics, or a ceramic coated diaphragm composed of the above diaphragm and ceramics and PVDF.

[0033] Beneficial effects achieved by the present invention:

[0034] (1) The battery power performance and heat dissipation performance have been greatly improved. Under the condition of 300-600A high current charge and discharge, the surface temperature of the positive and negative ends of the single battery is 35-60℃, which has excellent conductivity and heat dissipation capabilities. However, under the condition of 50A charge and discharge current, the temperature of the positive and negative ends of the battery prepared by the traditional flattening welding process exceeds 80℃.

[0035] (2) The short-circuit rate of the battery assembly process has been greatly reduced from 1-2% in the flattening welding process to 0.1-0.2%.

[0036] (3) The reliability of the battery structure is improved. The positive electrode current collector is connected to the collector plate through conductive glue, and the negative electrode is directly connected to the bottom of the shell through conductive glue. The silicone rubber and PVDF in the conductive glue play a role in bonding strength. The tensile strength between the positive electrode collector plate and the positive end of the electrode group, and the tensile strength between the negative end of the electrode group and the bottom of the steel shell are both greater than the flattening welding process.

[0037] (4) The consistent performance of the battery is improved. The conductive agent in the conductive glue has the function of conducting current and, in the injection process, the conductive agent has a huge specific surface area and can evenly guide the electrolyte into the electrode.

[0038] (5) The coating area of ​​the electrode is increased, and the battery capacity is 2-3.5% higher than that of the battery prepared by the flattening welding process. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1It is a schematic diagram of the structure of the cylindrical lithium-ion secondary battery in Example 1, wherein: 1-battery housing, 2-electrode group, 3-central steel tube, 4-first conductive glue, 5-second conductive glue, 6-positive electrode collector, 7-positive electrode ear, 8-combination cap, 9-CID sheet, 10-insulating gasket.

[0040] Figure 2 It is an expanded structural diagram of the electrode group in Example 1, wherein 11 is the negative electrode coating area, 12 is the copper foil, 13 is the separator, 14 is the positive electrode coating area, and 15 is the aluminum foil. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below with reference to specific embodiments, but is not intended to limit the scope of the present invention.

[0042] The experimental methods used in the following examples are conventional methods unless otherwise specified. The experimental raw materials and related equipment used in the following examples are all commercially available unless otherwise specified. Example

[0043] Example 1 provides a large-size power cylindrical lithium-ion battery, such as Figure 1 As shown, it includes a battery case 1, an electrode group 2 arranged in the battery case 1, a central steel pipe 3 in the electrode group 2, a first conductive glue 4 coated on the negative end surface of the electrode group 2, a second conductive glue 5 coated on the positive end surface of the electrode group 2, a positive current collecting plate 6, a positive electrode ear 7 on the positive current collecting plate 6, a combined cap 8 and a CID sheet 9 in the combined cap 8; the positive current collecting plate 6 is made of aluminum alloy, the positive electrode ear 7 is made of aluminum alloy, the positive current collecting plate 6 and the positive electrode ear 7 are fixed by laser welding, and an insulating gasket 10 is provided between the positive current collecting plate 6 and the positive electrode ear 7.

[0044] The positive electrode current collector 6 is connected to the positive terminal of the electrode group 2 through the second conductive adhesive 5, and the thickness of the conductive adhesive layer formed by the second conductive adhesive 5 is 0.3mm; the negative terminal of the electrode group 2 is connected to the inner surface of the battery housing 1 through the first conductive adhesive 4, and the thickness of the conductive adhesive layer formed by the first conductive adhesive 4 is 0.3mm. The first conductive adhesive 4 and the second conductive adhesive 5 are both composed of methyl vinyl silicone rubber, polyvinylidene fluoride particles, nano carbon black particles, carbon nanotubes and double two five initiator in a mass ratio of 29.8:20:25.0:25.0:0.2.

[0045] The electrode group 2 is formed by winding a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet. Figure 2It is an expanded structural diagram of the electrode group 2, wherein the negative electrode active material is coated on the copper foil 12 serving as the negative electrode sheet to form the negative electrode coating area 11, and the blank local width of the copper foil 12 is 3 mm; the width of each side of the diaphragm 13 exceeding the negative electrode coating area 11 is 1.5 mm, and the positive electrode active material is coated on the aluminum foil 15 serving as the positive electrode sheet to form the positive electrode coating area 14, and the blank area width of the aluminum foil is 4 mm; the width of each side of the negative electrode coating area 11 exceeding the positive electrode coating area 14 is 0.5 mm.

[0046] The production process of this large-size power cylindrical lithium-ion battery is as follows:

[0047] 1. Preparation of electrode group:

[0048] (1) Preparation of positive electrode sheet: Lithium iron phosphate, carbon nanotubes, and polyvinylidene fluoride were slurried in a mass ratio of 97.0:1.5:1.5, coated on a 15 μm thick carbon-coated aluminum foil, and rolled and cut to obtain a positive electrode sheet. The coating surface density of lithium iron phosphate, the active material of the positive electrode sheet, was controlled to be (125.0±2.5) mg / 10cm 2 ;

[0049] (2) Preparation of negative electrode sheet: Artificial graphite, nano carbon black particles, binder CMC, and binder SBR were homogenized in a mass ratio of 95.5:2.0:1.5:1.0, coated on a copper foil with a thickness of 8 μm, and rolled and cut to obtain a negative electrode sheet. The surface density of the negative electrode active material artificial graphite was controlled at (65.0±1.3) mg / 10cm 2 ;

[0050] (3) Winding the positive electrode sheet, the negative electrode sheet and the separator between the positive electrode sheet and the negative electrode sheet to form an electrode group, wherein the separator is a three-layer composite film of polypropylene-polyethylene-polypropylene with a thickness of 16 μm;

[0051] 2. Battery equipment: Glue coating on negative end of electrode group → electrode group into steel shell → high temperature melting and solidification of negative electrode glue → glue coating on positive end of electrode group → bonding of positive electrode collector → high temperature melting and solidification of positive electrode glue → roller trough → vacuum drying → electrolyte injection → sealing → formation and capacity separation.

[0052] The electrolyte solvent includes ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and ethyl acetate. The lithium salt is lithium hexafluorophosphate. The additives are propane sultone, vinylene carbonate, and lithium bis(fluorosulfonyl)imide. The mass percentage of each component is 10:35:20:10:15:3:3:4.

[0053] The only difference between Comparative Example 1 and Example 1 is that: no conductive glue is used, the positive and negative terminal surfaces are flattened by high-frequency oscillation, the positive electrode collector plate is laser welded to the positive terminal surface of the electrode group, the negative terminal surface of the electrode group is laser welded to the negative electrode collector plate, and the negative electrode collector plate is then spot-bottom welded to the inner surface of the steel shell.

[0054] Table 1 is a performance data comparison between Example 1 and Comparative Example 1, wherein the strength test method between the positive terminal surface of the electrode group and the current collecting plate is as follows: using an electronic tensile machine, the lower clamp fixes the electrode group, and the upper clamp fixes the current collecting plate. The upper clamp is lifted upward at a speed of 5 mm / min until the electrode group and the current collecting plate are completely separated, and the upper clamp stops running. The maximum value read is the strength between the positive terminal surface of the electrode group and the current collecting plate.

[0055] The strength test method between the negative terminal of the electrode group and the shell is the same as the strength test method between the positive terminal of the electrode group and the collector plate.

[0056] The charging current and temperature test method is as follows: In a 25°C constant temperature box, the battery in an empty state is charged at a certain constant current to a voltage of 3.6V, and the temperature of the positive and negative end surfaces is measured at the end of charging.

[0057] The discharge current and temperature test method is the same as the charge current and temperature test method.

[0058] Table 1

[0059] project Example 1 Comparative Example 1 Strength between the positive end of the electrode group and the collector plate <![CDATA[26.1Kg / mm 2 ]]> <![CDATA[7.6 Kg / mm 2 ]]> Strength of the negative end of the electrode group and the shell <![CDATA[26.5 Kg / mm 2 ]]> <![CDATA[18.5 Kg / mm 2 ]]> Charging Current vs. Temperature 300A / 35℃ positive terminal 300A / 38℃ negative terminal 30 A / 60℃ positive terminal 30 A / 60℃ negative terminal Discharge Current vs. Temperature 600 A / 56℃ positive terminal 600 A / 57℃ negative terminal 50A / 81℃ positive terminal 50A / 83℃ negative terminal

[0060] Although the present invention has been described in detail above by general description, specific implementation methods and experiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A cylindrical lithium-ion secondary battery, comprising a housing with an upper opening, a pole group disposed in the housing, a cap sealed at the upper opening of the housing, and a current collecting plate disposed between the positive terminal of the pole group and the cap, characterized in that: The negative terminal of the electrode group is bonded to the lower end of the shell by conductive adhesive, and / or the positive terminal of the electrode group is bonded to the current collecting plate by conductive adhesive; The conductive adhesive is made of raw materials of silicone rubber, polyvinylidene fluoride, inorganic conductive agent and initiator, wherein the mass ratio of the silicone rubber, polyvinylidene fluoride, inorganic conductive agent and initiator is 30-35:30-35:30-39:0.01-1.

2. The cylindrical lithium-ion secondary battery according to claim 1, characterized in that: The silicone rubber is methyl silicone rubber, methyl vinyl silicone rubber or methyl vinyl phenyl silicone rubber; And / or, the inorganic conductive agent is nano carbon black particles, carbon nanotubes, carbon fibers, graphene or VGCF; And / or, the initiator is di-tert-butylcumene peroxide, dicumyl peroxide, benzoyl peroxide or 2,4-dichlorobenzoyl peroxide.

3. The cylindrical lithium-ion secondary battery according to claim 1, characterized in that: The thickness of the conductive adhesive layer formed by any of the conductive adhesives is 0-1 mm; And / or, the electrode group includes a positive electrode sheet, a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet includes a positive electrode coating area coated with a positive electrode active material and a positive electrode blank area not coated with the positive electrode active material, the negative electrode sheet includes a negative electrode coating area coated with a negative electrode active material and a negative electrode blank area not coated with the negative electrode active material, wherein the width of the negative electrode blank area is 2-4mm, and either end of the separator exceeds the width of the negative electrode coating area by 1-2mm, the width of the positive electrode blank area is 3-5mm, and either end of the negative electrode coating area exceeds the width of the positive electrode coating area by 0.5-1mm.

4. The cylindrical lithium-ion secondary battery according to claim 3, characterized in that: The thickness of the conductive adhesive layer formed by any of the conductive adhesives is 0.1-0.5 mm.

5. A method for preparing a cylindrical lithium-ion secondary battery, characterized in that: The following steps are involved: (1) Winding a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet to form an electrode group, and coating the conductive adhesive according to claim 1 or 2 on the negative end of the electrode group; (2) placing the electrode group obtained in step (1) into a casing with an upper opening with the negative terminal facing downward, and subjecting the casing to high temperature treatment to solidify the conductive glue at the negative terminal; (3) The conductive adhesive of claim 1 or 2 is coated on the positive terminal of the electrode group, and then a current collecting plate is bonded to the positive terminal, and the conductive adhesive on the positive terminal is cured by high temperature treatment.

6. The preparation method according to claim 5, characterized in that: After step (3), the method further includes injecting electrolyte and sealing.

7. The preparation method according to claim 6, characterized in that: The electrolyte comprises a solvent, a soluble lithium salt and an additive, wherein the solvent is ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate or ethyl acetate, the soluble lithium salt is lithium hexafluorophosphate, and the additive is propane sultone, vinylene carbonate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, methylene disulfonate, lithium difluorooxalatophosphate or a fluorocarbonate.

8. The preparation method according to claim 5, characterized in that: The positive electrode sheet is composed of a positive electrode active material, a first conductive agent, a first binder and a first current collector.

9. The preparation method according to claim 8, characterized in that: The positive electrode active material is lithium iron phosphate, lithium manganese oxide, nickel cobalt manganese lithium or lithium cobalt oxide, the first conductive agent is nano carbon black particles, carbon nanotubes, carbon fibers, graphene or VGCF, the first binder is polyvinylidene fluoride, styrene butadiene rubber latex or polyolefin nitrile, and the first current collector is aluminum foil or carbon-coated aluminum foil.

10. The preparation method according to claim 9, characterized in that: The surface density of the positive electrode active material is 100-300 mg / 10 cm 2 .

11. The preparation method according to claim 5, characterized in that: The negative electrode sheet is composed of a negative electrode active material, a second conductive agent, a second binder and a second current collector.

12. The preparation method according to claim 11, characterized in that: The negative electrode active material is artificial graphite, natural graphite, mesophase carbon microspheres, silicon oxide, silicon carbide or lithium titanate, the second conductive agent is nano carbon black particles, carbon nanotubes, carbon fibers, graphene or VGCF, the second binder is sodium carboxymethyl cellulose, styrene-butadiene rubber latex, polyvinylidene fluoride or polyolefin nitrile, and the second current collector is copper foil.

13. The preparation method according to claim 5, characterized in that: The diaphragm is one or a composite of polypropylene film, polyethylene film, ceramic film and polyvinyl fluoride film.

Citation Information

Patent Citations

  • High-performance fluorine rubber composite material

    CN105419180A

  • Cylindrical lithium-ion battery

    CN202585597U

  • Cylindrical lithium ion secondary battery

    CN212648278U